Evaluating Employee Productivity in Labor Services at the Local Government Level - Suleman, Sukur; Hirto, Sahrony A. (Department of Government Studies, Universitas Muhammadiyah Buton., 2025)
Public employment services play a critical role in regional development, particularly in island areas where labor market dynamics are often under-researched. This study aims to evaluate employee productivity in labor services at the local government level, addressing a gap in the literature on bureaucratic performance in eastern Indonesia. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis at the Ternate City Manpower Office, Indonesia. The evaluation focused on four key indicators: human resource competence, facilities and infrastructure, workforce development programs, and outreach activities. Findings show that employee productivity is hindered by limited technical skills, inadequate infrastructure, budget constraints affecting program continuity, and weak communication strategies. Of 9,807 job seekers, only 1,712 were placed, while 1,952 vacancies remained unfilled—highlighting inefficiencies in labor market matching and service delivery. These structural and operational gaps reduce public trust and hinder employment outcomes. The study concludes that targeted reforms in human resource development, infrastructure investment, and strategic outreach are essential to improve service effectiveness. It recommends integrating digital labor market systems and strengthening partnerships with educational institutions to enhance responsiveness. These insights offer a replicable framework for improving employment services in other local government contexts facing similar challenges.